Effects of Bacillus subtilis-fermented soybean meal replacing fish meal on antioxidant activity, immunity, endoplasmic reticulum stress and hepatopancreas histology in Pacific white shrimp (Litopenaeus vannamei) - Songming Chen; Jieyu Dai; Yan Chen; Qiang Chen; Fen Dong; Congcong Wang; Yulong Sun; Jiteng Wang; Tao Han (Frontiers in Marine Science)
IntroductionScreening excellent bacterial strains for fermentation is the key to improving the nutritional value and bioavailability of soybean meal (SBM). This study investigated the application of Bacillus subtilis-fermented soybean meal (FSBM) on the feed of Pacific white shrimp (Litopenaeus vannamei).MethodsFSBM was used to replace 0%, 25%, 50%, 75%, and 100% fish meal, and the feeding trial was lasted for 8 weeks (initial weight: 0.9 g). Results and discussionThe amino acid profile in the whole shrimp body was tested. FSBM substitution only significantly reduced the content lysine in whole shrimp body, but increased the content of arginine. Fatty acid data showed that the content of n-6 PUFAs in whole shrimp was significantly increased by FSBM substitution. In muscle, FSBM substitution significantly reduced the content of MUFAs, but increased the content of PUFAs including C18:3n-3, C18:2n-6 and C20:4n-6. No hepatopancreas structure modifications appeared in the 25% group compared with the control group. Subsequently, we investigated the response patterns of different organs to FSBM substitution from antioxidant, endoplasmic reticulum stress and immunity. A high proportion of FSBM significantly reduced the content of GSH in hemolymph and hepatopancreas, while increased the mRNA expression of cat. FSBM substitution did not affect the activities of antioxidant enzymes in the intestine. However, the mRNA expression level of hsp70 in the intestine was significantly reduced by FSBM. In terms of immunity, the mRNA expression levels of lgbp and penaeidin in the hepatopancreas showed a significant linear increase trend. In muscle, high proportion of FSBM significantly increased the mRNA expression of imd. FSBM substitution did not significantly affect the expression of immune genes in the intestine. In terms of endoplasmic reticulum stress, FSBM substitution significantly increased the mRNA expression of eif2α in the hepatopancreas. In muscle, FSBM substitution inhibited the mRNA expression of bip. In the intestine, FSBM replacing 75% of fish meal significantly increased the mRNA expression of bip and ire1. In summary, this study indicated that when the fish meal content account for 40% in diets (dry weight), the screened Bacillus subtilis-FSBM can replace 25% of fish meal protein without reducing the antioxidant and immune abilities of shrimp.